Evaluating a smartphone application to improve child passenger safety and fire safety knowledge and behaviour. Issue 1 (5th September 2016) - Omaki, Elise; Shields, Wendy C; McDonald, Eileen; Aitken, Mary E; Bishai, David; Case, James; Gielen, Andrea
Abstract : Background: Although proven measures for reducing injury due to motor vehicle collision and residential fires exist, the number of families properly and consistently using child passenger restraints and smoke alarms remains low. This paper describes the design of the Safety In Seconds (SIS) 2.0 study, which aims to evaluate the impact of a smartphone app on parents' use of child restraints and smoke alarms. Methods: SIS is a multisite randomised controlled trial. Participants are parents of children aged 4–7 years who are visiting the Pediatric Emergency Department or Pediatric Trauma Service. Parents are randomised to receive tailored education about child passenger safety or about fire safety via the SIS smartphone app. A baseline and two follow-up surveys at 3 months and 6 months are conducted. Primary outcomes are: (1) having the correct child restraint for the child's age and size; (2) restraining the child in the back seat of the car; (3) buckling the child up for every ride; (4) having the restraint inspected by a child passenger safety technician; (5) having a working smoke alarm on every level of the home; (6) having hard-wired or lithium battery smoke alarms; (7) having and (8) practising a fire escape plan. Discussion: Finding ways to communicate with parents about child passenger and fire safety continues to be a research priority. This study will contribute to the evidence about how to promote benefits of proper and consistent child restraint and smoke alarm use. Trial registration number: NCT02345941 ; Pre-results.